Družbeno pospeševanje in vloga novinarstva v algoritemski prihodnosti - Amon Prodnik, Jernej (Javnost (Ljubljana), 2019)
Acceleration is a constitutive part of modern society, which has been observed by social scientists already in the 19th century. The article is based on a holistic definition of acceleration that uses Hartmut Rosa's theoretic model in which he separates between analytically distinct, but mutually dependent dimensions of acceleration. Amongst them is technological acceleration, where in communications telegraph and digitalization have had the most notable impact. Lately algorithms are seen as technologies with potential for a vast social impact. Their basic features in digital capitalism include: (1) opacity, (2) datafication, (3) automation, and (4) instrumental rationalization. Consequences of these characteristics are multifaceted, amongst them further push for acceleration because of automation. I then assess the relationship between journalism and time, which is inseparable from journalistic work. The need for immediacy, instantaneousness and promptness is not only a part of journalistic practice, but also ideological foundation of journalistic profession. This has consequences for its normative presuppositions, which will also be influenced by algorithms. I propose two speculative scenarions: pessimistic one, with further acceleration of journalistic work and mass layoffs, where algorithms are a replacement for journalists, and an optimistic one, where algorithms take over routine tasks and supplement their work, leading to a rise in quality.
Keywords: Algorithms; Algoritmi; Capitalism; čas; digitalizacija; Journalism; Kapitalizem; Modern society; Novinarstvo; Sodobna družba; Technological change; Tehnološke spremembe; tehnološki razvoj